Theoretical architecture based on emotional management (Agroindustria, Sociedad y Ambiente, 2022)
ABSTRACTThe management of university institutions faces great challenges motivated by a highly complex environment that is difficult to predict, which demands the consolidation of solid managerial competencies. In this sense, the present doctoral thesis was based on the interpretive paradigm under a qualitative approach, in the modality of the phenomenological-hermeneutical method with an emergent and flexible design, therefore, the study was developed in three (3) stages: descriptive, structural and exponential. The purpose of the study was to generate a theoretical architecture about managerial competencies in the university context based on emotional intelligence. The reality under study was assumed from the ontological foundation of intersubjective relativism with the social interaction of the actors, in addition to guiding the epistemological position from social constructionism. The social actors were represented by three (3) managers from the Francisco de Paula Santander University in Cúcuta, Colombia; The information gathering technique was the in-depth interview and categorization, coding and triangulation for its interpretation. The findings presented as a result of the understanding and interpretation of the discourse of the actors reflect the theoretical architecture, structured in introductory precision, propositional schemes, integral contribution, some macro-concepts such as: specific competencies to understand others and oneself, open management from potentiality of being by delegating functions, self-control of emotions for the manager's relational harmony and the creation of a positive atmosphere that, integrated into the ontological, epistemological and praxological pedestal, builds the construction of knowledge.
Keywords: management; managerial skills; emotional intelligence; university context